Adhesion of Candida albicans and Candida dubliniensis to acrylic and hydroxyapatite - Henriques, Mariana (2004)
The aim of this work was to compare the ability of strains of Candida albicans and Candida dubliniensis to adhere to acrylic and hydroxyapatite (HAP). In order to interpret the adhesion results, the surface properties of cells and materials were determined. Surface tension components (polar and apolar) and hydrophobicity were calculated through contact angle measurement and the elemental composition was determined by X-ray photoelectron spectroscopy (XPS). The results showed no significant differences in the number of adhered cells of both species to acrylic and hydroxyapatite. This was corroborated by the similarities in their surface properties and elemental composition. For both species, the adhesion to acrylic increased in the presence of artificial saliva due to the increase in the electron-donor capacity of this material. In the absence of artificial saliva, the number of adhered cells to HAP was greater than to acrylic, on account of the higher number of electron-donor groups of HAP. Hydrophobicity played a minor role in the adhesion process of both candidal species. Conversely, Lewis acid–base interactions seamed to govern this phenomenon.